Method for recovering zinc in ash content of waste tire pyrolysis carbon black and preparing zinc-aluminum hydrotalcite

The organic colloid layer on the cracked carbon black surface is removed by gentle sol agent and zinc-aluminum hydrotalcite is synthesized, which solves the problem of zinc volatility caused by high-temperature treatment, and improves the zinc recovery rate and the commercial value of the product.

CN119503861APending Publication Date: 2025-02-25BEIJING UNIV OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411657290.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When the prior art recycles zinc in the carbon black from used tires, high-temperature treatment leads to high-temperature volatility of zinc, reducing the recovery rate of zinc, and at the same time it is difficult to operate and easily leads to energy waste.

Method used

A gentle sol agent is used to remove the organic colloidal layer on the surface of the cracked carbon black, enhance the compatibility between the carbon black and the acid, and dissolve and leach the zinc element through hydrothermal reaction to synthesize zinc-aluminum hydrotalcite.

Benefits of technology

It improves zinc ions recovery, simplifies operating procedures, reduces energy consumption, and generates zinc-aluminum hydrotalcite with high commercial value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503861A_ABST
    Figure CN119503861A_ABST
Patent Text Reader

Abstract

The invention provides a method for recovering zinc in waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite. Comprising the following steps: 1) pretreating cracked carbon black; 2) dissolving and leaching metal elements; (3) iron element precipitation; and 4) preparing the zinc-aluminum hydrotalcite. The method solves the problems of resource waste, environmental pollution and the like of the existing waste tires, and is simple in operation process flow, low in cost and high in economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste tire treatment, and in particular relates to a method for recovering zinc from carbon black ash from waste tire pyrolysis and preparing zinc-aluminum hydrotalcite. Background Art

[0002] At present, the annual generation of waste tires exceeds tens of millions of tons, and this "black pollution" problem has brought tremendous pressure to the environment. Incorrect treatment of waste tires will cause huge safety hazards and waste of resources. For example, random stacking will occupy land, and random burning and burial will pollute the environment and endanger human health. Therefore, the reuse of waste tires has become an urgent problem to be solved.

[0003] The products of waste tire thermal cracking are mainly cracking oil, cracking gas, steel wire and cracking carbon black. After deep processing, cracking carbon black can be used for tire reinforcement, adsorbent, ink printing, etc. There is a big difference between cracking carbon black and commercial carbon black. The surface of cracking carbon black contains an organic colloid layer, which makes its surface hydrophobic and not compatible with acids and alkalis. It also has the disadvantages of large particle size, small specific surface area, low structural degree and low surface functional group activity, which is the key to its reinforcement performance.

[0004] Usually, the ash content of pyrolysis carbon black is about 20%, which is much higher than that of commercial carbon black. The ash content is mainly composed of inorganic oxides such as ZnO, ZnS, SiO2, and also contains elements such as Ca, Fe, Cu, S, among which the content of Zn is 8%-10%. To reduce the ash content of pyrolysis carbon black, acid (hydrochloric acid, nitric acid and sulfuric acid) washing, double acid (hydrochloric acid and hydrofluoric acid) leaching and acid-base (hydrochloric acid and sodium hydroxide) combined leaching methods are usually used. These methods can remove most of the ash and improve the reinforcing performance of pyrolysis carbon black on rubber, but there is a colloid layer on the surface of pyrolysis carbon black, which prevents carbon black from contacting with acid and alkali, and acid washing and alkali washing modification will waste a lot of acid and alkali. At the same time, the wastewater needs to be treated without pollution, and the experimental operation is extremely difficult, thus causing environmental pollution.

[0005] In response to the above problems, Chinese patent CN 203508014 U has designed a new type of equipment for ash reduction and desulfurization of waste tire pyrolysis carbon black. The ash content of the treated carbon black is significantly reduced, and the sulfur content is also greatly reduced, which greatly improves the quality of carbon black. Chinese patent application CN 110760204 A proposes a system and method for reducing the ash content of waste tire pyrolysis carbon black and recovering zinc. The pyrolysis carbon black is reprocessed in a vacuum distillation chamber. Under a high-temperature vacuum environment, the carbon black in the pyrolysis carbon black undergoes a carbon thermal reduction reaction with zinc oxide to generate zinc and vaporize it at high temperature, condense and recover it, and at the same time, vaporize it at high temperature to remove the residual oil in the carbon black. However, although these high-temperature treatment technologies can more thoroughly remove the colloidal layer on the surface of the pyrolysis carbon black, they also cause the zinc sulfide therein to be vaporized, which is difficult to handle and easily causes energy waste, reducing the recovery rate of zinc.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The object of the present invention is to provide a method for recovering zinc from the ash of carbon black cracked by waste tires and preparing zinc-aluminum hydrotalcite, wherein a mild sol is used to leach the cracked carbon black, remove the surface organic layer, enhance the compatibility of the cracked carbon black with the aqueous solution, and retain the zinc in the carbon black. At the same time, the zinc in the cracked carbon black ash is recovered and a zinc-aluminum bimetallic layered hydroxide hydrotalcite is synthesized. The hydrotalcite has the characteristics of controllable particle size, uniform dispersion of metal active components, and exchangeable interlayer anions. Therefore, it can be used as a catalyst, flame retardant, adsorbent, etc. in multiple fields.

[0008] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0009] The present invention provides a method for recovering zinc from carbon black ash from waste tire pyrolysis and preparing zinc-aluminum hydrotalcite, comprising the following steps:

[0010] 1) Pretreatment of pyrolysis carbon black: adding a sol to the pyrolysis carbon black of waste tires, performing a hydrothermal reaction, removing the surface organic colloid layer, and obtaining a pretreatment pyrolysis carbon black material;

[0011] 2) dissolving and leaching metal elements: adding the pretreated cracked carbon black material obtained in step 1) to a dissolving acid for reaction, dissolving and leaching metal elements in the carbon black ash, and obtaining a leaching filtrate I;

[0012] 3) Precipitation of iron: adding a precipitant to the leaching filtrate I obtained in step 2), adjusting the pH value of the solution until the iron element is completely precipitated, and separating the zinc-containing filtrate II;

[0013] 4) Preparation of zinc-aluminum hydrotalcite: adding aluminum salt and urea to the zinc-containing filtrate II obtained in step 3) to carry out hydrothermal reaction, cooling, and drying to obtain zinc-aluminum hydrotalcite.

[0014] Preferably, in step 1), the mass ratio of the pyrolysis carbon black to the volume ratio of the sol agent (g:mL) is 1:5-1:10; wherein the sol agent comprises one or more of methanol, ethanol, isopropanol, ether, acetone and toluene, with a mass fraction of 30%-50%.

[0015] Preferably, in step 1), the hydrothermal reaction temperature is 80-150° C., and the hydrothermal reaction time is 4-8 h.

[0016] Preferably, in step 2), the dissolving acid is hydrochloric acid and / or nitric acid, and the concentration thereof is 2-5 mol / L.

[0017] Preferably, in step 2), the volume ratio of the mass of the pretreated pyrolysis carbon black material to the dissolved acid solution (g:mL) is 1:8-1:14.

[0018] Preferably, in step 2), the reaction temperature is 45-85°C, the reaction time is 6-10h, and the stirring speed is 300-900r / min.

[0019] Preferably, in step 3), the precipitant is concentrated ammonia water (containing 25% to 28% ammonia), sodium hydroxide or potassium hydroxide or other alkali solution, and the pH is adjusted to 7.0.

[0020] Preferably, in step 3), the water bath heating temperature is 65-85° C. and the time is 4-8 h.

[0021] Preferably, in step 4), the aluminum salt includes aluminum chloride or aluminum nitrate, etc. The amount of aluminum salt and urea is determined according to the concentration of zinc ions, and the ratio is a conventional method in the art, and the molar amount of urea is usually twice the molar amount of zinc salt and aluminum salt anions.

[0022] Preferably, in step 4), the hydrothermal reaction temperature is 90-130° C., and the reaction time is 4-8 h.

[0023] Beneficial effects of the present invention:

[0024] 1) The present invention utilizes an organic solvent to remove the organic colloid layer on the surface of the cracked carbon black, thereby enhancing the compatibility of the carbon black with the acid and preventing the high-temperature volatilization of zinc.

[0025] 2) The zinc element in the ash of the pyrolysis carbon black of the present invention can be efficiently leached and further formed into zinc-aluminum layered hydroxide hydrotalcite, thereby expanding the application scope of the pyrolysis carbon black. The generated hydrotalcite has high commercial value.

[0026] 3) The present invention aims to improve the current problems of waste of resources, environmental pollution, etc. of waste tires, with simple operation process, low cost and high economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] First, the present invention is explained as a whole, as follows:

[0031] The present invention adds a sol under mild conditions to remove the organic colloid layer on the surface of the cracked carbon black, enhances the compatibility of the carbon black with acid, and facilitates the leaching of zinc ions. The zinc element in the ash of the cracked carbon black is leached under different reaction conditions (dissolving acid concentration, mass volume ratio, reaction time, reaction temperature), and the zinc ion concentration is determined by EDTA titration. Aluminum salts (such as aluminum chloride, aluminum nitrate, etc.) and urea are added to the obtained zinc-containing filtrate to synthesize zinc-aluminum hydrotalcite. Figure 1 It is a process flow chart of the present invention, and the specific steps are as follows:

[0032] (1) Add a sol to the waste tire pyrolysis carbon black, mix and place in a reactor for 6-8 hours to allow the sol to fully react with the colloid layer on the surface of the carbon black, and dry in a drying oven at 80°C overnight to obtain a solid product I.

[0033] (2) adding the solid product I to different dissolving acids and stirring for reaction, dissolving and leaching the metal elements in the ash of the cracked carbon black; filtering the treated slurry to obtain the solid product II and the leaching filtrate I;

[0034] (3) adding a precipitant (e.g., alkaline solution such as ammonia water, sodium hydroxide, potassium hydroxide, etc.) to the leaching filtrate I to adjust the pH so that the iron therein is completely precipitated, heating in a water bath to completely separate the precipitate from the filtrate, and filtering to obtain the zinc-containing filtrate II and FeOOH;

[0035] (4) Take 10 mL of zinc-containing filtrate II for EDTA complex titration, add Na2S2O3 solution to mask the copper ions in the filtrate, and add saturated NaF solution to mask the aluminum ions in the filtrate. Calculate the concentration of zinc ions in the filtrate by the volume of EDTA consumed, repeat three times and take the average value to determine the concentration of zinc ions in the solution;

[0036] (5) adding a certain amount of aluminum salt and urea to the zinc-containing filtrate II, reacting in a hydrothermal reactor for several hours, cooling to room temperature, and washing and drying the obtained solid to obtain zinc-aluminum hydrotalcite;

[0037] The sol used in step (1) can be one or more of methanol, ethanol, isopropanol, ether, acetone and toluene, the volume ratio of the mass of the pyrolysis carbon black to the sol is 1:5-1:10, the reaction temperature is 80-150°C, and the reaction time is 4-8h.

[0038] The acid used in step (2) is hydrochloric acid and / or nitric acid, with a concentration of 2-5 mol / L, a volume ratio of the mass of the pyrolyzed carbon black to the dissolved acid solution g:mL of 1:8-1:14, a reaction temperature of 45-85°C, a reaction time of 6-10h, and a stirring speed of 300-900r / min.

[0039] The ammonia water added in step (3) is concentrated ammonia water, containing 25% to 28% ammonia, and the pH is adjusted to 7.0. The water bath heating temperature is 65-85° C. and the time is 4-8 hours.

[0040] In step (5), the hydrothermal reaction temperature is 90-130° C. and the reaction time is 4-8 h.

[0041] The pyrolysis carbon black obtained by the treatment of the present invention can be used as a reinforcing filler for rubber tires and as an adsorbent to remove pollutants in water bodies such as methyl orange and heavy metal ions; the obtained zinc-aluminum hydrotalcite can be used as a catalyst carrier to catalyze various chemical reactions, and can be used as an adsorbent to remove pollutants in water bodies after calcination, and can also be used in the fields of batteries and capacitors.

[0042] The present invention aims to solve the problems of resource waste and environmental pollution in the treatment of waste tires. Through simplified operation process and low cost investment, the output of high value-added products is achieved, and the economic benefits are remarkable. It is estimated that for every ton of pyrolysis carbon black processed, about 14.86 kg of zinc-aluminum hydrotalcite can be prepared. This process not only greatly reduces acid and alkali consumption and raw material waste, but also realizes the recycling of zinc elements, effectively reduces production costs, and embodies the concept of green circular economy.

[0043] Example 1

[0044] A method for recovering zinc from carbon black ash from waste tire pyrolysis and preparing zinc-aluminum hydrotalcite, the specific operation is as follows:

[0045] (1) Waste tire pyrolysis carbon black and 30% by mass of isopropanol sol were mixed in a solid-liquid ratio of 1:5 and placed in a reactor at 85° C. for 6 hours. After the reaction, the mixture was filtered and dried to obtain pyrolysis carbon black with the colloid layer removed, i.e., solid product I.

[0046] (2) adding 2 mol / L hydrochloric acid solution to the solid product I to react, wherein the mass volume ratio of the solid product I to the hydrochloric acid solution is 1:10, the treatment temperature is 55° C., the time is 8 h, the stirring speed is 600 r / min, and the metal and non-metal elements in the ash in the pyrolysis carbon black are leached to obtain a solid product II and a leaching filtrate I;

[0047] (3) adding concentrated ammonia water to the leaching filtrate I to adjust the pH to 7.0, so that the iron therein is completely precipitated, heating in a water bath at 85° C. for 4 h to completely separate the precipitate from the filtrate, and filtering to obtain the zinc-containing filtrate II and FeOOH;

[0048] (4) Na2S2O3 solution was added to the zinc-containing filtrate II to mask the copper ions in the filtrate, and saturated NaF solution was added to mask the aluminum ions in the filtrate. The concentration of zinc ions in the solution was determined by EDTA complexometric titration; and the recovery rate of zinc ions was calculated to be 73.7%.

[0049] (5) Aluminum chloride and urea were added to the zinc-containing filtrate II, and the mixture was reacted at 100° C. for 5 h in a hydrothermal reactor, cooled to room temperature, and the obtained white solid was washed and dried to obtain zinc-aluminum hydrotalcite. The yield of zinc-aluminum hydrotalcite synthesized from leaching 1 kg of cracked carbon black was calculated to be 12.65 g.

[0050] Comparative Example 1

[0051] A method for recovering zinc from carbon black ash from waste tire pyrolysis and preparing zinc-aluminum hydrotalcite, the specific operation is as follows:

[0052] (1) The waste tire pyrolysis carbon black was heated at 600°C for 1.5 min in an air atmosphere, sprayed with water mist to cool it to room temperature, and the surface colloid layer was removed;

[0053] (2) adding the treated pyrolysis carbon black into a 2 mol / L hydrochloric acid solution for reaction, wherein the solid-liquid ratio is 1:10, the treatment temperature is 55° C., the time is 8 h, and the stirring speed is 600 r / min, to leach the metal and non-metal elements in the ash in the pyrolysis carbon black;

[0054] (3) adding concentrated ammonia water to the obtained leaching filtrate to adjust the pH to 7.0 to completely precipitate the iron therein, heating in a water bath at 85° C. for 4 h to completely separate the precipitate from the filtrate, and filtering to obtain a zinc-containing filtrate and FeOOH;

[0055] (4) Na2S2O3 solution was added to the zinc-containing filtrate to mask the copper ions in the filtrate, and saturated NaF solution was added to mask the aluminum ions in the filtrate, and the concentration of zinc ions in the solution was determined by EDTA complexometric titration; the recovery rate of zinc ions was calculated to be 65.2%; compared with Example 1, it can be seen that the recovery rate of zinc ions is reduced, and the high temperature treatment causes part of the zinc to be vaporized and volatilized;

[0056] (5) Aluminum chloride and urea were added to the zinc-containing filtrate, and the mixture was reacted in a hydrothermal reactor at 110° C. for 5 h, cooled to room temperature, and the obtained white solid was washed and dried to obtain zinc-aluminum hydrotalcite. The yield of zinc-aluminum hydrotalcite synthesized from leaching 1 kg of cracked carbon black was 9.57 g.

[0057] Example 2

[0058] A method for recovering zinc from carbon black ash from waste tire pyrolysis and preparing zinc-aluminum hydrotalcite, the specific operation is as follows:

[0059] (1) Waste tire pyrolysis carbon black and 40% by mass of toluene sol were mixed in a solid-liquid ratio of 1:6 in a reactor at 100° C. for 6 h. After the reaction, the mixture was filtered and dried to obtain pyrolysis carbon black with the colloid layer removed, i.e., solid product I.

[0060] (2) adding 3 mol / L nitric acid solution to the solid product I for reaction, wherein the mass volume ratio of the pyrolysis carbon black to the nitric acid solution is 1:12, the treatment temperature is 55° C., the time is 8 h, and the stirring speed is 600 r / min, so as to leach the metal elements in the ash in the pyrolysis carbon black;

[0061] (3) adding concentrated ammonia water to the obtained leaching filtrate to adjust the pH to 7.0 to completely precipitate the iron therein, heating in a water bath at 85° C. for 4 h to completely separate the precipitate from the filtrate, and filtering to obtain zinc-containing filtrate II and FeOOH;

[0062] (4) Na2S2O3 solution was added to the zinc-containing filtrate II to mask the copper ions in the filtrate, and saturated NaF solution was added to mask the aluminum ions in the filtrate. The concentration of zinc ions in the solution was determined by EDTA complexometric titration; and the recovery rate of zinc ions was calculated to be 78.9%;

[0063] (5) Aluminum nitrate and urea were added to the zinc-containing filtrate II, and the mixture was reacted at 90° C. for 8 h in a hydrothermal reactor, cooled to room temperature, and the obtained white solid was washed and dried to obtain zinc-aluminum hydrotalcite. The yield of zinc-aluminum hydrotalcite synthesized from leaching 1 kg of cracked carbon black was 14.86 g.

[0064] Comparative Example 2

[0065] A method for recovering zinc from carbon black ash from waste tire pyrolysis and preparing zinc-aluminum hydrotalcite, the specific operation is as follows:

[0066] (1) The waste tire pyrolysis carbon black was heated at 800°C for 1 min in a nitrogen atmosphere, sprayed with water mist to cool it to room temperature, and the surface colloid layer was removed;

[0067] (2) adding 3 mol / L nitric acid solution to the treated pyrolysis carbon black for reaction, wherein the mass volume ratio of pyrolysis carbon black to nitric acid solution is 1:12, the treatment temperature is 55° C., the time is 8 h, the stirring speed is 600 r / min, and the metal elements in the ash in the pyrolysis carbon black are leached;

[0068] (3) adding concentrated ammonia water to the obtained leaching filtrate to adjust the pH to 7.0 to completely precipitate the iron therein, heating in a water bath at 85° C. for 4 h to completely separate the precipitate from the filtrate, and filtering to obtain a zinc-containing filtrate and FeOOH;

[0069] (4) Na2S2O3 solution was added to the zinc-containing filtrate to mask the copper ions in the filtrate, and saturated NaF solution was added to mask the aluminum ions in the filtrate. The concentration of zinc ions in the solution was determined by EDTA complexometric titration, and the recovery rate of zinc ions was calculated to be 67.4%. Compared with Example 2, it can be seen that the recovery rate of zinc ions is reduced, and the high temperature treatment causes part of the zinc to be vaporized and volatilized;

[0070] (5) Aluminum nitrate and urea were added to the zinc-containing filtrate, and the mixture was reacted at 90° C. for 8 h in a hydrothermal reactor, cooled to room temperature, and the obtained white solid was washed and dried to obtain zinc-aluminum hydrotalcite. The yield of zinc-aluminum hydrotalcite synthesized from leaching 1 kg of cracked carbon black was 9.43 g.

[0071] It can be seen that the presence of the colloid layer on the surface of the pyrolysis carbon black hinders the reaction between the carbon black and the acid, resulting in the inability to completely remove the ash in the carbon black during the acid leaching process, and then recover the zinc therein. Although the high-temperature treatment of the prior art can remove the colloid layer on the surface of the carbon black, the high temperature easily causes the zinc sulfide in the ash of the pyrolysis carbon black to vaporize and volatilize, resulting in a lower zinc recovery rate, and the operation is difficult, which easily leads to a waste of energy and resources.

[0072] The present invention adopts a mild sol to remove the colloidal layer on the surface of cracked carbon black at 80-150° C. It can be seen from the embodiments and comparative examples that the zinc ion recovery rate obtained by the method of sol treatment is higher, the operation is simple, the energy consumption is reduced, the yield of the synthesized zinc-aluminum hydrotalcite is higher, and it can be applied to catalysts, flame retardants, adsorbents and other applications in multiple fields.

[0073] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for recovering zinc from carbon black ash from waste tire pyrolysis and preparing zinc-aluminum hydrotalcite, comprising the following steps: 1) Pretreatment of pyrolysis carbon black: adding a sol to the pyrolysis carbon black of waste tires, performing a hydrothermal reaction, removing the surface organic colloid layer, and obtaining a pretreatment pyrolysis carbon black material; 2) dissolving and leaching metal elements: adding the pretreated cracked carbon black material obtained in step 1) to a dissolving acid for reaction, dissolving and leaching metal elements in the carbon black ash, and obtaining a leaching filtrate I; 3) Precipitation of iron: adding a precipitant to the leaching filtrate I obtained in step 2), adjusting the pH value of the solution until the iron element is completely precipitated, and separating the zinc-containing filtrate II; 4) Preparation of zinc-aluminum hydrotalcite: adding aluminum salt and urea to the zinc-containing filtrate II obtained in step 3) to carry out hydrothermal reaction, cooling, and drying to obtain zinc-aluminum hydrotalcite.

2. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 1), the mass ratio of the pyrolysis carbon black to the volume ratio of the sol agent is 1:5-1:10; wherein the sol agent includes one or more of methanol, ethanol, isopropanol, ether, acetone and toluene, with a mass fraction of 30%-50%.

3. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 1), the hydrothermal reaction temperature is 80-150° C. and the hydrothermal reaction time is 4-8 h.

4. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 2), the dissolving acid is hydrochloric acid and / or nitric acid, and the concentration thereof is 2-5 mol / L.

5. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 2), the volume ratio of the mass of the pretreated pyrolysis carbon black material to the dissolved acid solution is 1:8-1:14 (g:mL).

6. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 2), the reaction temperature is 45-85°C, the reaction time is 6-10h, and the stirring speed is 300-900r / min.

7. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 3), the precipitant is concentrated ammonia water, sodium hydroxide or potassium hydroxide, and the pH is adjusted to 7.

0. Preferably, the concentrated ammonia water contains 25% to 28% ammonia.

8. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 3), the water bath heating temperature is 65-85° C. and the time is 4-8 h.

9. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 4), the aluminum salt includes aluminum chloride or aluminum nitrate.

10. The method for recovering zinc from waste tire pyrolysis carbon black ash and preparing zinc-aluminum hydrotalcite according to claim 1, characterized in that: In step 4), the hydrothermal reaction temperature is 90-130° C. and the reaction time is 4-8 h.

Citation Information

Patent Citations

  • System and method for reducing ash content of pyrolysis carbon black of waste tires and recovering Zn

    CN110760204A

  • Novel equipment for deashing and desulfurizing carbon black generated by pyrolysis of scrap tires

    CN203508014U